Challenging inequity in mathematics education by making pedagogy more visible to learners. Issue 2 (7th February 2022) - Wright, Pete; Fejzo, Alba; Carvalho, Tiago
ABSTRACT: This paper reports on initial findings from the Visible Maths Pedagogy research project, a collaboration between an academic researcher and two teacher researchers (the paper's authors). The aim of the project was to explore the effects of making pedagogy more visible on students' success in school mathematics. We adopted a Participatory Action Research methodology to plan and evaluate five strategies used alongside 'progressive' teaching approaches to make the teacher's pedagogical rationale more visible to learners. Our findings show that students, particularly those from disadvantaged backgrounds, were initially prone to misinterpret the intentions of the teacher. However, the five strategies helped students gain a greater appreciation of the teacher's pedagogical rationale and how to respond appropriately. We discuss the implications of these findings for enabling all students to access the benefits of progressive teaching approaches and for opening up to scrutiny what it means to be a successful learner of mathematics.